Generation Y Employees Saving Behaviour: Finance Technology-enabled Services in South Sulawesi, Indonesia - Rohani, Rohani; HS, Sri Wahyuni; Asriyana, Asriyana; Ilyas, Muh. Indra Fauzi (Universitas Pendidikan Nasional, 2025)
This study was motivated by the low level of saving behavior among millennial workers in the formal sector, despite their broad access to digital financial services. The purpose of this research was to analyze the determinants of saving behavior among millennial employees in South Sulawesi by emphasizing the roles of financial literacy, financial product knowledge, and technology-enabled financial services innovation as a mediating variable. A quantitative approach with a survey method was employed, and the sampling technique used was purposive sampling, involving 316 respondents working in the formal sector across Makassar City, Gowa Regency, and Maros Regency. Data were collected through a five-point Likert-scale questionnaire measuring four key constructs: financial literacy, financial product knowledge, technology-enabled financial services innovation, and saving behavior. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicated that both financial literacy and financial product knowledge had positive and significant effects on saving behavior, either directly or indirectly through technology-enabled financial services innovation. Financial product knowledge exerted the strongest influence on saving behavior. The study contributed theoretically by integrating the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) to explain financial behavior among millennials in a developing country context. Practically, the findings provided insights for financial institutions and policymakers to design integrated financial literacy programs and digital financial innovations that effectively promote sustainable saving behavior in the digital economy era.